2021
DOI: 10.21037/jtd-20-3034
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment patterns and outcomes in small-cell lung cancer: a systematic literature review

Abstract: Background: Small-cell lung cancer (SCLC) accounts for 12-15% of lung cancers and is associated with poor survival outcomes and high symptom burden. This study employed a broad, systematic search strategy and timeframe to identify evidence on real-world treatment patterns and outcomes for SCLC outside the USA, including understanding sub-populations such as extensive-stage (ES) or limited-stage (LS) disease. Methods: Databases (MEDLINE, Embase, and EBM reviews) were searched for journal articles published in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 83 publications
0
11
0
2
Order By: Relevance
“…22,23 A recent review of real-world evidence of treatment patterns and outcomes reported that these had remained poor over the preceding 20 years but they did not present their results by age. 24 Our results should be interpreted considering contemporary practice. The calendar period of the study pre-dated the routine use of immunotherapy.…”
Section: Noteci: Confidence Intervalmentioning
confidence: 78%
See 1 more Smart Citation
“…22,23 A recent review of real-world evidence of treatment patterns and outcomes reported that these had remained poor over the preceding 20 years but they did not present their results by age. 24 Our results should be interpreted considering contemporary practice. The calendar period of the study pre-dated the routine use of immunotherapy.…”
Section: Noteci: Confidence Intervalmentioning
confidence: 78%
“…22,23 A recent review of real-world evidence of treatment patterns and outcomes reported that these had remained poor over the preceding 20 years but they did not present their results by age. 24…”
Section: Discussionmentioning
confidence: 99%
“…Clinical impact of SCLC covariates on prognosis have previously been studied with Cox regression. 8 , 27 , 28 , 29 In fact, the previous work with this cohort explored hazard ratios of patients with LD/ED receiving chemotherapy. 22 RSF was adopted in this work to compute feature importance of covariates that provided statistical significant hazard ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Small cell lung cancer (SCLC) is a highly heterogeneous malignancy of neuroendocrine origin accounting for approximately 15% of all cases of lung cancer. SCLC is characterised by the early development of metastases, rapid recurrence and a low survival rate (1)(2)(3)(4). The 5year overall survival rate in SCLC barely reaches 5%, while average overall survival reaches only 2 to 4 months in untreated patients (1,5,6).…”
Section: Introductionmentioning
confidence: 99%